Congruence Properties of Combinatorial Sequences via Walnut and the Rowland-Yassawi-Zeilberger Automaton - Rampersad, Narad; Shallit, Jeffrey (The Electronic Journal of Combinatorics, 2022)
Certain famous combinatorial sequences, such as the Catalan numbers and the Motzkin numbers, when taken modulo a prime power, can be computed by finite automata. Many theorems about such sequences can therefore be proved using Walnut, which is an implementation of a decision procedure for proving various properties of automatic sequences. In this paper we explore some results (old and new) that can be proved using this method.